Robust Nanostructured Silver and Copper Fabrics with Localized Surface Plasmon Resonance Property for Effective Visible Light Induced Reductive Catalysis. Issue 6 (7th January 2016) - Anderson, Samuel R.; Mohammadtaheri, Mahsa; Kumar, Dipesh; O'Mullane, Anthony P.; Field, Matthew R.; Ramanathan, Rajesh; Bansal, Vipul
Abstract : Inspired by high porosity, absorbency, wettability, and hierarchical ordering on the micrometer and nanometer scale of cotton fabrics, a facile strategy is developed to coat visible light active metal nanostructures of copper and silver on cotton fabric substrates. The fabrication of nanostructured Ag and Cu onto interwoven threads of a cotton fabric by electroless deposition creates metal nanostructures that show a localized surface plasmon resonance (LSPR) effect. The micro/nanoscale hierarchical ordering of the cotton fabrics allows access to catalytically active sites to participate in heterogeneous catalysis with high efficiency. The ability of metals to absorb visible light through LSPR further enhances the catalytic reaction rates under photoexcitation conditions. Understanding the modes of electron transfer during visible light illumination in Ag@Cotton and Cu@Cotton through electrochemical measurements provides mechanistic evidence on the influence of light in promoting electron transfer during heterogeneous catalysis for the first time. The outcomes presented in this work will be helpful in designing new multifunctional fabrics with the ability to absorb visible light and thereby enhance light‐activated catalytic processes. Abstract : Endowing cotton fabrics with multifunctionality through intelligent engineering is highly desired. In this article, large area Cu@Cotton and Ag@Cotton fabrics are fabricated with interesting properties, including visible light absorption and a large number of catalytic sites to promote heterogeneous catalysis with good robustness. The influence on electron transfer through localized surface plasmon resonance of Cu and Ag enhances the catalytic degradation of ferricyanide in an aqueous environment.